A Question-Answering System for Legal Information Retrieval - Quaresma, Paulo (2012)
In this paper we present a question-answering system for Portuguese juridical documents. The system has two modules: preliminary analysis of documents (information extraction) and query processing (information retrieval). The proposed approach is based on computational linguistic theories: syntactical analysis (constraint grammars); followed by semantic analysis using the discourse representation theory; and, finally, a semantic/pragmatic interpretation using ontologies and logical inference. Knowledge representation and ontologies are handled through the use of an extension to PROLOG, ISCO, which allows to integrate logic programming and external databases. In this way it is possible to solve scalability problems like the need to represent more than 10 millions of discourse entities. The system was evaluated with the complete set of decisions from several Portuguese juridical institutions (Supreme Courts, High Court, Courts, and Attorney-General's Office) in a total of 180,000 documents. The obtained results were quite interesting and motivating and allowed the identification of some strong and weak characteristics of the system.